Identification with Authority and the Transindividual in Rousseau: Critical Comments on Balibar's Concept of the Transindividual. Issue 1 (2nd January 2018) - Tegos, Spyridon
Abstract: In his essay, 'Aimances de Rousseau: Sur La Nouvelle Héloise comme traité des passions, ' Etienne Balibar analyses the structure of transition from love to friendship which are more than passions or sentiments; they are affective structures, interconnected within an affective network the political relevance of which transcends the dichotomy between the domestic and political sphere. Belonging to the genre of sentimental novel, Rousseaus Nouvelle Héloise transgresses the canonical structure of the genre in the eighteenth century. His innovative literary strategy, according to Balibar, consists in creating couples and triangles of egalitarian and hierarchical status that cannot be considered independently but exclusively through their relational nature. This critical review focuses on the 'figures of authority' involved in La Nouvelle Héloise that parallel the figure of the legislator in the Social Contract . I argue that Rousseau struggles with the riddle of deference to auctoritas that does not undermine the basic principles of republican citizenship. I suggest that in Rousseau's guiding thread, rites and ceremonies amount to founding cultural myths that are indispensable for any individual and collective relational identity. Reclaiming a psychoanalytic interpretation of the charismatic leader, Freudian figures of authority attract Balibar's attention regarding the perilous, unquestioned forms of mass identification they trigger. In this vein, I claim that identification with the prestigious authority of an allegoric 'legislator' as depicted in the Social Contract also amounts to a conceptual 'line of flight' in Rousseau, indispensable to conceive plainly the unsettling potential of transindividuality.